Data Security Management of the Academic Information System at Kuningan University (SIKADUKU) Using the DAMA-DMBOK Framework - Khalimi, Toni (Journal of Artificial Intelligence and Software Engineering, 2025)
Data security management is crucial for an information system, considering that data that has been transformed into information can be accessed by any user. Data security management protects information assets in alignment with privacy and confidentiality regulations as well as business needs. Poor data security management can negatively impact ongoing management processes.  Therefore, data management, particularly data security, is necessary as a preventive measure and a solution to data-related issues and their security. Several frameworks can be applied to manage data security, one of which is DAMA-DMBOK. By utilizing two knowledge areas within the DAMA-DMBOK framework, namely Data Governance and Data Security Management, for an academic information system, a proposed recommendation for governance and data security management design can be formulated for the Academic Information System (SIA) of Universitas Kuningan (SIKADUKU).